Abnormal thyroid function parameters in the second trimester of pregnancy are associated with breech presentation at term: a nested cohort study. (April 2016) - Vissenberg, Rosa; Vrijkotte, Tanja G.M.; van der Post, Joris A.M.; Fliers, Eric; Goddijn, Mariette; Bisschop, Peter H.
Abstract: Objective: Thyroid dysfunction has been described as a possible risk factor for having an abnormal fetal position at birth. In this study we aim to determine the association between thyroid function in early pregnancy and breech presentation at term. Study design: We used data from the Amsterdam Born Children and their Development (ABCD) cohort. 3347 pregnant women were included between January 2003 and March 2004 in Amsterdam, the Netherlands. Thyroid function tests were performed between 5 and 37 weeks gestational age (median 12.9 weeks). The main outcome measure was the association between thyroid function in early pregnancy and breech presentation at term. Univariate and multivariate analysis were performed to determine the association between thyroid function and breech presentation. Results: Increased TSH in pregnancy, defined as thyroid stimulating hormone (TSH) >97.5th percentile (>3.53 mIU/L), was associated with a higher risk for breech presentation at term (aOR 2.32, CI 1.1–4.8, p  = 0.02) compared to euthyroidism (TSH between 2.5th and 97.5th percentile). After exclusion of overt hypothyroidism and hyperthyroidism the aOR was 2.34 (CI 1.1–5.0, p  = 0.03). Trimester specific analysis showed a significant association of increased TSH levels (>3.68 mIU/L) in the second trimester with breech presentation (aOR 3.7, CI 1.7–7.8, p  = 0.001). In the second trimester low free thyroxine (FT4) <2.5th percentile (<6.7 pmol/L) was also associated with breech presentation (aOR 2.5, CI 1.0–6.3, p  = 0.04). Conclusions: Increased TSH and decreased FT4 in the second trimester of pregnancy are associated with an increased risk for breech presentation at term. The association of abnormal thyroid parameters in the first of third trimester is still unclear.